History and Politics in French-Language Comics and Graphic Novels - McKinney, Mark (University Press of Mississippi, 2008)
With Essays by Baru, Bart Beaty, Cécile Vernier Danehy, Hugo Frey, Pascal Lefèvre, Fabrice Leroy, Amanda Macdonald, Mark McKinney, Ann Miller, and Clare Tufts In Belgium, France, Switzerland, and other French-speaking countries, many well-known comics artists have focused their attention on historical and political events. In works ranging from comic books and graphic novels to newspaper strips, cartoonists have addressed such controversial topics as French and Belgian collaboration and resistance during World War II, European colonialism and U.S. imperialism, anti-Semitism in France, the integration of African immigrant groups in Europe, and the green and feminist movements. History and Politics in French-Language Comics and Graphic Novelscollects new essays that address comics from a variety of viewpoints, including a piece from practicing artist Baru. The explorations range from discussion of such canonical works as Hergé'sTintinseries to such contemporary expressions as Baru'sRoad to America(2002), about the Algerian War. Included are close readings of specific comics series and graphic novels, such as Cécile Vernier Danehy's examination of Cosey'sSaigon Hanoi, about remembering the Vietnam War. Other writers use theoretical lenses as a means of critiquing a broad range of comics, such as Bart Beaty's Bourdieu-inspired reading of today's comics field, and Amanda Macdonald's analysis of bandes dessinées (French comic books) in New Caledonia during the 1990s. The anthology establishes the French-language comics tradition as one rich with representations of history and politics and is one of the first English-language collections to explore the subject. Mark McKinney is associate professor of French at Miami University, Ohio. With Alec G. Hargreaves, he editedPost-Colonial Cultures in France.